2020
DOI: 10.1073/pnas.2003358117
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic loss of the transfer RNA-modifying enzyme TYW2 induces ribosome frameshifts in colon cancer

Abstract: Transfer RNA (tRNA) activity is tightly regulated to provide a physiological protein translation, and tRNA chemical modifications control its function in a complex with ribosomes and messenger RNAs (mRNAs). In this regard, the correct hypermodification of position G37 of phenylalanine-tRNA, adjacent to the anticodon, is critical to prevent ribosome frameshifting events. Here we report that the tRNA-yW Synthesizing Protein 2 (TYW2) undergoes promoter hypermethylation-associated transcriptional silencing in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 56 publications
(83 reference statements)
2
33
0
Order By: Relevance
“…Extending from these findings, it may be inferred that the frameshifting efficiency of imG-14 in taxol resistant strains is theoretically higher than OHyW in wide type cells. Moreover, the latest study showed that loss of TYW2 increases the -1 programmed ribosome frameshifting frequency and is associated with poor survival in colorectal cancer patients ( 62 ). Taken together, TYW2 downregulation induced chemotherapy (taxol)-resistance may be another possible explanation for poor clinical outcomes in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Extending from these findings, it may be inferred that the frameshifting efficiency of imG-14 in taxol resistant strains is theoretically higher than OHyW in wide type cells. Moreover, the latest study showed that loss of TYW2 increases the -1 programmed ribosome frameshifting frequency and is associated with poor survival in colorectal cancer patients ( 62 ). Taken together, TYW2 downregulation induced chemotherapy (taxol)-resistance may be another possible explanation for poor clinical outcomes in patients.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of cancer changes the tRNA modification chemistry, which occurs after oxidative stress ( Endres et al, 2019 ). Increasing evidence argues that tRNA modification and corresponding tRNA-modifying enzymes not only play an important role in translation but also are important signal molecules in the pathogenesis of cancer ( Rashad et al, 2020 ; Rosselló-Tortella et al, 2020 ; Zhang et al, 2020c ). Dong et al found that the modification profiles of tRNA in rapidly proliferating cancer cells were roughly the same, indicating that there was a proliferation-related modification regulation in rapidly proliferating cancer cells, and tRNA had a positive regulatory effect in rapidly proliferating cancer cells ( Dong et al, 2016 ).…”
Section: Roles Of Trna Metabolism In Lung Cancermentioning
confidence: 99%
“…Of note, tRNAs will be cleaved into fragments with regulatory functions under stress conditions [4][5][6] . In general, normal tRNA metabolism is essential to maintain the stability and functions of tRNA molecules, while the defects in certain tRNA biogenesis proteins cause various human diseases, including cancer, neurological disorders, immunodeficiency, and diabetes mellitus [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%